KNOWLEDGE SHARING MODEL AMONG ACADEMIC STAFFS IN UNIVERSITIES - Semlinda Juszandri Bulan; Dana Indra Sensuse (Jurnal Sistem Informasi, 2012)
Knowledge sharing is very important in an organization, one of the effects of these activities is to improve the performance of the organization. In education sector, effective knowledge sharing among academic staff can improve the performance of a college. This research proposed a model for knowledge sharing among academic staff, firstly the factors that influence knowledge sharing consists of individual factors, organizational factors and technological factors and secondly relationship between knowledge sharing and organizational performance.